2016
DOI: 10.1016/j.nbd.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Tau knock-in mice display frontotemporal dementia relevant behaviour and histopathology

Abstract: Models of Tau pathology related to frontotemporal dementia (FTD) are essential to determine underlying neurodegenerative pathologies and resulting Tauopathy relevant behavioural changes. However, existing models are often limited in their translational value due to Tau overexpression, and the frequent occurrence of motor deficits which prevent comprehensive behavioural assessments. In order to address these limitations, a forebrain-specific (CaMKIIα promoter), human mutated Tau (hTauP301L+R406W) knock-in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 109 publications
7
61
0
Order By: Relevance
“…Overall, our data lend direct support to the patho-physiological relevance of non-filamentous, oligomeric tau. Nevertheless, strong correlations with cognitive decline were also observed for conformational and phospho-tau as previously reported in humans [25, 30] and animal models [43, 44, 83]. Our data expand on the suggested disruptive role of monomeric phospho-tau [41], and suggest oligomerization caused by pathological modification of monomeric tau to play a key role.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our data lend direct support to the patho-physiological relevance of non-filamentous, oligomeric tau. Nevertheless, strong correlations with cognitive decline were also observed for conformational and phospho-tau as previously reported in humans [25, 30] and animal models [43, 44, 83]. Our data expand on the suggested disruptive role of monomeric phospho-tau [41], and suggest oligomerization caused by pathological modification of monomeric tau to play a key role.…”
Section: Discussionsupporting
confidence: 89%
“…The amygdala is involved in creating, maintaining and modifying anxiety and fear responses. Furthermore, increased anxiety is commonly observed in patients with Alzheimer’s disease or frontotemporal lobar degeneration (FTLD) (Porter et al , 2003), and increased anxiety-like behaviour has been found in FTLD-Tau mouse models, as assessed by the elevated plus maze (Walf and Frye, 2007; Koss et al , 2016). Age-matched pR5 mice were split into four treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety-like behaviour was assessed by the elevated plus maze as previously described (Koss et al , 2016) with some changes. Briefly, mice were placed in the central area of the maze (elevated cross-shaped apparatus with a central square, and closed as well as open arms with unprotected edges).…”
Section: Methodsmentioning
confidence: 99%
“…Second, tTA/WT12 mice display early deficits in cognitive function, most remarkably impaired working memory, a frontal cortex-dependent function. They also show signs of a mild decrease in anxiety in the elevated plus maze test, which some authors interpret as disinhibition and might indicate alterations in amygdala or prefrontal cortex function (Roberson, 2012; Koss et al, 2016). These phenotypes are consistent with those observed in other FTD mouse models (Takeuchi et al, 2011; Przybyla et al, 2016; Vernay et al, 2016a), although in some FTD models an increase in anxiety was also reported (Koss et al, 2016; Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our behavioral data from tTA/WT12 mice constitutes further evidence for a link between TDP-43 dysregulation and sociability. A forebrain specific, human mutated Tau (hTauP301L + R406W) knock-in mouse showed FTD-relevant phenotypes related to semantic memory, anxiety, anhedonia, sleep and activity (Koss et al, 2016), and mice expressing human P301S mutant tau protein recapitulated neurological deficits of human tauopathies, including early abnormalities in the open field test, the elevated plus-maze test, Y-maze test, Barnes maze test and the Morris water maze test (Takeuchi et al, 2011). Importantly, most of these studies were performed when motor deficits were not preeminent, although in some cases detailed characterization was not reported, in contrast to the current analysis of tTA/WT12 mice.…”
Section: Discussionmentioning
confidence: 99%